Peran Media Sosial TikTok Dalam Meningkatkan Partisipasi Politik Mahasiswa Geografi Stambuk 2022 Fakultas Ilmu Sosial Universitas Negeri Medan. - Yoga, Muhammad Yoga Pratama; Hasibuan, Rahma Yani; Siregar, Dewi Sartika; Butar Butar, Ikhsanul Fadly; Halking (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2024)
This study examines the role of TikTok in enhancing political participation among students, specifically among Geography students from the 2022 cohort at the Faculty of Social Sciences, Universitas Negeri Medan. Using a descriptive qualitative approach with triangulation techniques (interviews, observations, and documentation), the research found that TikTok positively contributes to deepening students' political understanding, increasing their awareness of political issues, and encouraging involvement in political discussions. Overall, TikTok proves effective in increasing political participation, but improvements in information verification are necessary to maximize its educational role. Kata Kunci : TikTok, political participation, students, political content, media literacy.